Confucius: A Philosophy of Life in Chinese Society - Rasyid, Hemas Mutia; Lestari, Fitri Khairunisa (Confucius Institute Universitas Sebelas Maret, 2023)
The country of China is the birthplace of the leading philosophers, one of whom is Kong Zi, better known as Confucius. By his wisdom, he was entrusted as Minister of Public Works, Commissioner of Police, and Minister of Justice by the king during the Zhou Dynasty when he was 35 to 60. This research aims to explain Kong Zi's philosophy of life as profoundly as possible using data collection that has been studied. The analysis is written using a qualitative method of data collection. After Kong Zi did not serve in government, he wrote a lot and published books about poetry and poetry. This great philosopher also often takes time to share knowledge with his disciples. Kong Zi teaches his pupils first to understand life and relations with fellow human beings. The Confucian view of life emphasizes life in the world by not involving mystical things, and advancing critical thinking makes Confucius look more modern. The popularity of the philosophy of life by the Confucian to this day is still widely used by many people.